Financial determinants of consumer price inflation. What do dynamics in money, credit, efficiency and size tell us? - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
Purpose The purpose of this paper is to examine the effects of financial dynamic policy options in money, credit, efficiency and size on consumer prices. Soaring food prices have marked the geopolitical landscape of developing countries in the past few years. Design/methodology/approach The estimation approach used is a Two-Stage-Least Squares Instrumental Variable technique. Instruments include: legal-origins; income-levels and religious-dominations. The first-step consists of justifying the choice of the estimation approach with a Hausman-test for endogeneity. In the second-step, we verify that the instrumental variables are exogenous to the endogenous components of explaining variables(financial dynamic channels) conditional on other covariates(control variables). In the third-step, the validity of the instruments is examined with the Sargan overidentifying restrictions test. Robustness checks are ensured by: (1) use of alternative indicators of each financial dynamic; (2) estimation with robust Heteroscedasticity and Autocorrelation Consistent (HAC) standard errors; and (3) adoption of two interchangeable sets of instruments. Findings Findings broadly reveal the following: (1) money(depth) and credit(activity) which are in absolute measures have positive elasticities of inflation; while (2) financial efficiency and size in relative measures have negative elasticities of inflation. Social implications This paper helps in providing monetary policy options in the fight against soaring consumer prices. By keeping inflationary pressures on food prices in check, sustained campaigns involving strikes, demonstrations, marches, rallies and political crises that seriously disrupt economic performance could be mitigated. Originality/value As far as we have perused, there is yet no study that assesses monetary policy options that could be relevant in addressing the dramatic surge in the price of consumer commodities.
Keywords: E31; G20; O10; O55; P50; 330; Banks; Inflation; Development; Panel; Africa